Quantification of viable Brochothrix thermosphacta in cooked shrimp and salmon by real-time PCR - Mamlouk, Kelthoum, K.; Mace, Sabrina, S.; Guilbaud, Morgan, M.; Jaffres, Emmanuel, E.; Ferchichi, Mounir, M.; Prévost, Herve, H.; Pilet, Marie-France, M.-F.; Dousset, Xavier, X. (Food Microbiology, 2012)
Brochothrix thermosphacta, a Cram-positive bacterium, is considered as the predominant spoilage microbiota of modified atmosphere packing (MAP) shrimp and fish. Traditional methods currently used to detect B. thermosphacta in foods are time-consuming and labour-intensive. The aim of this study was to develop a real-time PCR quantification method combined with a propidium monoazide (PMA) sample treatment step to monitor the population of B. thermosphacta in cooked shrimp and salmon. The specificity of the two primers M0405 and M0404 used to amplify a 70 bp fragment of the 16S rRNA gene was demonstrated by using purified DNA from 30 strains, among 21 bacterial species including 22 reference strains. Using these primers for real-time PCR and in pure culture, a good correlation was obtained between real-time PCR and the conventional plating method. Quantification was linear over 7-log units using artificially inoculated samples. The method performed successfully when tested on naturally contaminated cooked shrimp and fresh salmon, with a minimum threshold of 1.9 x 10(2) CFU/g for accurate quantification of B. the rmosphacta. The correlation between the B. thermosphacta counts obtained by real-time PCR and plate counts on naturally contaminated shrimp and salmon was high (R-2=0.895). Thus, this study presents a rapid tool for producing reliable quantitative data on B. thermosphacta in cooked shrimp and fresh salmon. (C) 2011 Elsevier Ltd. All rights reserved.